KESALAHAN BERBAHASA DALAM SKRIPSI MAHASISWA PRODI PENDIDIKAN BAHASA DAN SASTRA INDONESIA UNIVERSITAS TIDAR - Irsyadi Shalima; Asri Wijayanti (Fakultas Keguruan dan Ilmu Pendidikan, 2020)
Students of the Indonesian Language and Literature Education Study Program (PBSI) should master scientific writing in Indonesian. However, the facts on the ground are different. There are many language errors found in student theses. This study aims to describe the language errors of PBSI students in their thesis. By knowing the types of students' language errors in their thesis, Indonesian language learning, especially writing skills, can be improved in the future. Therefore, this research is beneficial for students, teachers, and lecturers. This research was conducted qualitatively with data sources obtained through population and sampling techniques. The data source is the student's thesis of PBSI, so the data is in the form of written language. Meanwhile, the research data analysis used the agih method with the lesap technique, the ganti technique, and the ubah wujud technique. The results of this study are the existence of language errors at various linguistic levels, namely phonology, morphology, and syntax. Language errors at the morphological level are in the form of errors in the use of punctuation marks. Errors at the morphological level are in the form of errors in the affixation process. Meanwhile, errors at the syntactic level are in the form of errors in the sentence composing process.